2010
DOI: 10.2478/s11536-009-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous reporting of adverse drug reactions at a department of Internal Medicine

Abstract: AbstractThe aim of the present study was to characterize the pattern of adverse drug reactions (ADRs) reported in a university teaching hospital in south-east Serbia. The study was conducted based on ADRs reported during a six-month period to the ADR reporting unit of the university clinical center. Evaluation of data was done for various parameters, such as patient demographics, drug and reaction characteristics, and outcome of reactions. Assessment was also done for causality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…10 The study had limitations, shows that the number of cases reported is few due to unrecognized ADRs, under reporting of ADRs followed by phobia by the treating doctors not to report as it may cause bad reputation. Most of the ADRs were Probable based followed by Certain in our study which was similar to study done by Jovic et al 11…”
Section: Discussionsupporting
confidence: 90%
“…10 The study had limitations, shows that the number of cases reported is few due to unrecognized ADRs, under reporting of ADRs followed by phobia by the treating doctors not to report as it may cause bad reputation. Most of the ADRs were Probable based followed by Certain in our study which was similar to study done by Jovic et al 11…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that health care professionals from Bosnia and Herzegovina had the lowest response rate to the questionnaires sent (22). A study from Serbia, a neighboring country to Bosnia and Herzegovina, published in 2010, also showed a low rate of hospital ADR reporting in Serbia in comparison to other countries (23). The results of a survey on hospital pharmacists' services conducted by the European Association of Hospital Pharmacists, showed a low rate of ADR related services in Bosnia and Herzegovina (24).…”
Section: Discussionmentioning
confidence: 97%
“…4 In the USA, ADEs account for nearly 100 000 emergency hospitalisations each year in this age group. 5 Different approaches exist for estimating medication harm resulting in hospitalisation, such as medical record reviews, [6][7][8][9][10][11][12] analysis of spontaneous reporting data, [13][14][15][16][17][18][19] and identification of ADE-related codes from the International Classification of Diseases (ICD) on inpatient records. [20][21][22][23][24][25][26] Some of these methods are labour-intensive, whereas others are subject to under-reporting and selection bias.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches exist for estimating medication harm resulting in hospitalisation, such as medical record reviews, analysis of spontaneous reporting data, and identification of ADE‐related codes from the International Classification of Diseases (ICD) on inpatient records . Some of these methods are labour‐intensive, whereas others are subject to under‐reporting and selection bias …”
Section: Introductionmentioning
confidence: 99%